The Relationship Between Interpersonal Communication and Assertive Behavior With Intrapersonal Conflict - Katarina Rizky Sri Mumpuni; Suharsono Suharsono; Daniel Purwoko Budi (INJECT (Interdisciplinary Journal of Communication), 2023)
Interpersonal communication and assertive behavior with intrapersonal conflict in employees are important factors in the work atmosphere, of one of the state-owned banks. Quantitative method research with multiple linear regression analysis techniques on the three variables. Based on the results of the analysis that have a highly significant negative relationship between interpersonal communication and assertive behavior with intrapersonal conflict in employees, and partially a highly significant negative between interpersonal communication and intrapersonal conflict, and there is no relationship between assertive behavior and intrapersonal conflict in employees at one of the state-owned banks.